The Effectiveness of Indigenous African Values in Building the Resilience of Out-Of-School Suspended Learners - Methi, Lina Mmakgabo (Central European Journal of Educational Research, 2025)
This study explores the effectiveness of indigenous African values in building the resilience of suspended learners in South African township schools. Schools often impose suspensions in response to a wide range of behaviour challenges established by legislators and officials to address problems related to school interruptions. Nevertheless, despite the established disciplinary procedures, students still exhibit difficult behaviour. This study aimed to examine the effectiveness of African Indigenous values in building the resilience of suspended learners. The study comes from larger research that focuses on the experiences of suspended learners in the context of township secondary schools. This research study is qualitative in nature to provide a rich description of the parents' experiences in their natural setting. I used a purposive sample of parents of suspended learners based on the characteristics of the population and the objective of the study. I collected data using face-to-face interviews, field notes, and documents. The collected data was organised, organized, prepared systematically, and classified into themes and categories. The findings showed that given the increasing number of suspended learners in township schools, parents and the school community recognised the need to understand the risk factors that contribute to behaviour problems as a stepping stone to building the resilience of adolescents.